2021
DOI: 10.1007/s43832-021-00003-5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals risk assessment of water and sediments collected from selected river tributaries of the Mara River in Tanzania

Abstract: This study investigated the levels of Pb, Hg, Cr, Cd, and As in water and sediments from the tributaries of the Mara River, Tanzania. Pollution risk of water and sediments was investigated using seven indices and five metals. During the dry period, the highest concentration of Pb, Hg, Cr, Cd, and As in sediments was 17.45 ± 1.22, 0.01, 1.56 ± 0.5, 1.3 ± 0.09, and 30.81 ± 0.02 mg/kg, respectively. During the wet period, the highest concentration of Pb, Hg, Cr, Cd, and As in sediments was 4.37 ± 0.28, 0.012, 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The mean concentration of As (Tranca Grande: 4.62 ± 0.24, Tipicocha: 6.95 ± 0.57, Pomacocha: 3.27 ± 0.45 mg kg −1 ) and Cd (Tranca Grande: 0.18 ± 0.01, Tipicocha: 0.18 ± 0.01, Pomacocha: 0.17 ± 0.01 mg kg −1 ) exceeded upper continental crustal reference values (UCC) (As: 1.5 and Cd: 0.098 mg kg −1 ). These results are similar to those obtained by [45] who reported As and Cd concentrations in sediments higher than the interim sediment quality guidelines. The high concentration of As in lake sediments could be attributed to anthropogenic activities such as intensive fish farming and agriculture that misuse arsenic fertilizers and pesticides [7] and Cd could be due to low input from streams to lagoons causing precipitation of Cd in the sediments, increasing its concentration [34] .…”
Section: Resultssupporting
confidence: 91%
“…The mean concentration of As (Tranca Grande: 4.62 ± 0.24, Tipicocha: 6.95 ± 0.57, Pomacocha: 3.27 ± 0.45 mg kg −1 ) and Cd (Tranca Grande: 0.18 ± 0.01, Tipicocha: 0.18 ± 0.01, Pomacocha: 0.17 ± 0.01 mg kg −1 ) exceeded upper continental crustal reference values (UCC) (As: 1.5 and Cd: 0.098 mg kg −1 ). These results are similar to those obtained by [45] who reported As and Cd concentrations in sediments higher than the interim sediment quality guidelines. The high concentration of As in lake sediments could be attributed to anthropogenic activities such as intensive fish farming and agriculture that misuse arsenic fertilizers and pesticides [7] and Cd could be due to low input from streams to lagoons causing precipitation of Cd in the sediments, increasing its concentration [34] .…”
Section: Resultssupporting
confidence: 91%
“…The concentrations of heavy metals in the sampling area were also compared to background values [19], Table 4. It was observed that apart from Bon Accord Creek (MVC4), all the sampling sites in the study area had at least one heavy metal above the background level (Table 4), suggesting that there were probably some anthropogenic inputs at the sites [34]. According to results in Table 4, Bolivar Creek (MVC25) and Beaver Creek (MVC33) had at least nine heavy metals at each site above the TEL/LEL hence these sites were considered the most polluted.…”
Section: Physiochemical Parametersmentioning
confidence: 99%
“…Also, the analysis of various pollution indices used in the present study for sediment quality addresses the gaps that exist in the literature in the study area. According to Harikumar et al, [5] as cited by Nkinda et al, [34], pollution indices are powerful tools for evaluating, developing, and conveying raw environmental data into more meaningful information for politicians and decision-makers.…”
Section: Introductionmentioning
confidence: 99%
“…where PRI is the potential ecological risk index of multiple heavy metals; E r i is the risk factor of heavy metal i; T r i is the toxic coefficient of heavy metal i (i.e., Cd = 30, Hg = 40, As = 10, Pb = Cu = 5, Cr = 2, and Zn = 1) [4,15,21,22]; C i is the same as in Equation (1); C i B is the geochemical background value of i, which was used the average value of surface soil in Hebei province [23]. According to the value of E r i and PRI, the degree of potential ecological risk can be divided into different levels (Table S3).…”
Section: Ecological Risk Assessment Of Heavy Metalsmentioning
confidence: 99%